4(2x-4)-3(x-2)=-2(4x+15)

Simple and best practice solution for 4(2x-4)-3(x-2)=-2(4x+15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-4)-3(x-2)=-2(4x+15) equation:


Simplifying
4(2x + -4) + -3(x + -2) = -2(4x + 15)

Reorder the terms:
4(-4 + 2x) + -3(x + -2) = -2(4x + 15)
(-4 * 4 + 2x * 4) + -3(x + -2) = -2(4x + 15)
(-16 + 8x) + -3(x + -2) = -2(4x + 15)

Reorder the terms:
-16 + 8x + -3(-2 + x) = -2(4x + 15)
-16 + 8x + (-2 * -3 + x * -3) = -2(4x + 15)
-16 + 8x + (6 + -3x) = -2(4x + 15)

Reorder the terms:
-16 + 6 + 8x + -3x = -2(4x + 15)

Combine like terms: -16 + 6 = -10
-10 + 8x + -3x = -2(4x + 15)

Combine like terms: 8x + -3x = 5x
-10 + 5x = -2(4x + 15)

Reorder the terms:
-10 + 5x = -2(15 + 4x)
-10 + 5x = (15 * -2 + 4x * -2)
-10 + 5x = (-30 + -8x)

Solving
-10 + 5x = -30 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-10 + 5x + 8x = -30 + -8x + 8x

Combine like terms: 5x + 8x = 13x
-10 + 13x = -30 + -8x + 8x

Combine like terms: -8x + 8x = 0
-10 + 13x = -30 + 0
-10 + 13x = -30

Add '10' to each side of the equation.
-10 + 10 + 13x = -30 + 10

Combine like terms: -10 + 10 = 0
0 + 13x = -30 + 10
13x = -30 + 10

Combine like terms: -30 + 10 = -20
13x = -20

Divide each side by '13'.
x = -1.538461538

Simplifying
x = -1.538461538

See similar equations:

| 2x^2+5x-0.33=0 | | -4a=-24 | | 5-4y-y=-29 | | 5+z=5 | | -3x+6=31+2x | | 2y+3x=10 | | 2x^2+13x+15= | | 2x^2+5x-0.66=0 | | 7(-3x+4)= | | -24=6-15-5a | | 2x-y=-15 | | -3y+2=-4 | | R+3=17 | | -7x+9=-4x-3 | | 23x-16=14-7x | | x^2+x^2+9=89 | | x+9=-36+6x | | 4+3x=7x+4 | | 7y=-28+7 | | 5x(3x+8)=4 | | 3x+7=12+4x | | 6x-5=3+5x | | x(x+3)-2=2+x(x+1) | | y=x^2+2x-15 | | 3x+2=3x+56 | | 9x=9y-18 | | (40x^2-13x+1)=0 | | 20-x=3(x-4) | | x^2-8x-19=0 | | x/4+3x/4-2x/4+x/4= | | -5x+6=-71+6x | | v-1-1=-7 |

Equations solver categories